Complete mitochondrial genome sequence and phylogenetic analysis of Anisarchus medius (Reinhardt, 1837). Issue 2 (3rd July 2019) - Liu, Kun; Lin, Heshan; Wang, Jianjun; Sun, Jun
Abstract: Anisarchus medius (Reinhardt, 1837) has been identified as a target species for investigating the effects of climate change on population patterns in coastal Arctic ecosystems. The complete mitochondrial genome of the Anisarchus medius was first sequenced in this study. The mitochondrial genome was sequenced with 16, 524 bp in length, including 13 protein-coding genes, 22 transfer RNA genes, two ribosomal RNA genes, and a putative control region. All the protein-coding genes employed ATG as the start codon except COI using GTG. Three stop codons were observed in the protein-coding genes, including TAA, TAG and T. In addition, phylogenetic tree can provide further genetic analysis for this important species.